2020
DOI: 10.1021/acsphotonics.0c00140
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced near-Infrared Photoresponse from Nanoscale Ag-Au Alloyed Films

Abstract: Alloying of metals provides a vast parameter space for tuning of material, chemical, and mechanical properties, impacting disciplines ranging from photonics and catalysis to aerospace. From an optical point-of-view, pure thin metal films yield enhanced light absorption due to their cavity effects. However, an ideal metal–semiconductor photodetector requires not only high absorption, but also long hot carrier attenuation lengths in order to efficiently collect excited carriers. Here we demonstrate that Ag-Au al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…One of the most common examples are the superabsorbers, [19] which will be discussed in Section 4.1. More recently, the benefits of using ultrathin metallic films to increase light absorption in the NIR range of the electromagnetic spectrum have been demonstrated in sys tems ranging from hotcarrier devices composed by Si/ultrathin layers of metals and alloys [27,68] to indexnearzero substrate and ultrathin metals. [69] In these devices, the large optical absorp tion results from the combined effect of large optical attenua tion within the lossy thinfilm material (e.g., semiconductors or metals) and the nontrivial interface phase shifts.…”
Section: Experimental Determination Of Dielectric Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most common examples are the superabsorbers, [19] which will be discussed in Section 4.1. More recently, the benefits of using ultrathin metallic films to increase light absorption in the NIR range of the electromagnetic spectrum have been demonstrated in sys tems ranging from hotcarrier devices composed by Si/ultrathin layers of metals and alloys [27,68] to indexnearzero substrate and ultrathin metals. [69] In these devices, the large optical absorp tion results from the combined effect of large optical attenua tion within the lossy thinfilm material (e.g., semiconductors or metals) and the nontrivial interface phase shifts.…”
Section: Experimental Determination Of Dielectric Functionsmentioning
confidence: 99%
“…In the past, there have been various reports on the direct calculation of the band structure of alloys using density func tional theory (DFT). [52,65] As a very recent example, Krayer et al [68] have shown explicitly how each metal contributes to the overall band structure of the Ag-Au alloys. As presented in Figure 3h, Au dominates most of the highenergy states in the alloy's dband, whereas comparable contributions from Au and Ag are observed for other states across all critical points of the Brillouin zone.…”
Section: Electronic Band Structurementioning
confidence: 99%
See 2 more Smart Citations
“…These carriers are generated in the mid-infrared and near-infrared range, and subsequent engineering of the electronic and optical properties by alloying them with other noble metals has emerged as a route for the efficient generation of hot carriers as this procedure brings the positions of the d-band closer to the Fermi level, E F [28][29][30][31]. Consequently it reduces the interband energy threshold, permitting the efficient generation of long-lived hot carriers in the infrared and near-infrared region [32,33].…”
Section: Introductionmentioning
confidence: 99%